2014
DOI: 10.1007/8904_2014_338
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhosis Associated with Pyridoxal 5′-Phosphate Treatment of Pyridoxamine 5′-Phosphate Oxidase Deficiency

Abstract: We report the case of an 8-year-old boy with pyridoxamine 5 0 -phosphate oxidase (PNPO) deficiency. He developed seizures at 24 h of age that were refractory to standard anticonvulsant therapy and a trial of pyridoxine but responded to pyridoxal phosphate (PLP) at 28 days of life. Genetic testing identified compound heterozygous mutations in the PNPO gene. Management of encephalopathic episodes required escalation of PLP dose to 100 mg/kg/day by 2 years of age. Routine blood tests at this time showed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…Details of the initial presentation of case 4 have been reported previously (Hoffmann et al 2007;Schmitt et al 2010;Sudarsanam et al 2014). Intractable neonatal seizures occurred, with a number of different seizure types seenabnormal eye movements, abnormal smiling, multifocal myoclonic jerks, focal clonic seizures and spasms associated with screaming and irritability.…”
Section: Casementioning
confidence: 98%
See 1 more Smart Citation
“…Details of the initial presentation of case 4 have been reported previously (Hoffmann et al 2007;Schmitt et al 2010;Sudarsanam et al 2014). Intractable neonatal seizures occurred, with a number of different seizure types seenabnormal eye movements, abnormal smiling, multifocal myoclonic jerks, focal clonic seizures and spasms associated with screaming and irritability.…”
Section: Casementioning
confidence: 98%
“…A trial of withdrawal of PLP at 8 months of age was associated with recurrence of encephalopathy, and PLP has subsequently been continued (doses ranging from 50 to 100 mg/kg/day in divided doses). However, at age 2 years, as a result of concerns about hepatotoxicity (Sudarsanam et al 2014), lower PLP doses were given more frequently (on a 4 hourly basis including an overnight dose) and the total daily dose was decreased to 50-60 mg/kg/day. During infancy, episodes of encephalopathy were relatively frequent and often associated with febrile illnesses, but after 18 months of age these became less frequent and abated with careful management of PLP dosage and timing of administration.…”
Section: Casementioning
confidence: 99%
“…8,9 There have also been several reports of liver toxicity with prolonged highdosage use of PLP, 10, 11 but overall pyridoxine and PLP supplementation are generally well tolerated. 7,8,10,12 To our knowledge, no bleeding symptoms have been reported in those taking either pyridoxine or PLP.…”
Section: Discussionmentioning
confidence: 74%
“…Previous reports2 have linked PLP supplementation to the risk of permanent hepatic injury. In the clinical report by Sudarsanam et al ,3 the liver biopsy showed early cirrhosis, which was attributed to the PLP therapy. The PLP dose was in fact reduced to 60 mg/kg/day and although the liver function tests improved, they did not normalise, showing persistent evidence of hepatic fibrosis and portal hypertension.…”
Section: Discussionmentioning
confidence: 95%